Using Audio Visual Media to Improve English Learning Outcomes - Sarah Maulida; Muhamad Sofian Hadi (Jurnal Studi Guru dan Pembelajaran, 2022)
Video recordings, slides, and sound are examples of audio-visual media. It is thought that learning to use audio visuals in English lessons will help students better understand the problems or lessons presented. Because listeners are encouraged to use their imagination and optimize their left and right brain function. Audio-visual media in the form of animated learning videos and power points are used in English subjects at SMK Grafika that are conducted online or online. The purpose of this study was to see if audio visuals could boost students' motivation and enthusiasm for learning during online classes.